Tax Accounting in Support of the National Strategy for Optimizing State Revenue - Muammar Khaddafi (Journal of Economics, Management, Development, and Education, 2026)
This study aims to analyze the role of tax accounting in supporting the government's national strategy for optimizing state revenue and fiscal reform in Indonesia. The focus of the study is on how the quality of tax accounting influences reporting effectiveness, taxpayer compliance, and its contribution to increasing the tax ratio and achieving tax revenue targets in the State Budget. This study uses a qualitative method with a descriptive-analytical approach, through literature studies, analysis of fiscal policy documents, and interpretation of Indonesian tax revenue and tax ratio data for the 2022–2025 period. The results indicate that tax accounting plays a strategic role as a measurement, reporting, and control instrument that supports increased tax compliance and transparency. However, the implementation of tax accounting in Indonesia still faces obstacles such as regulatory complexity, uneven taxpayer data quality, limited tax literacy, and a gap in tax administration digitalization. This study concludes that strengthening tax accounting through standardization, digitalization, education, and risk-based supervision can be a crucial factor in strengthening state revenue and supporting the success of the national fiscal reform strategy.